A nanoscale oxide-based broadband optical detector - Hessell, Edward (2017)
Optical detectors are quickly advancing through the years, with developments in optoelectronics allowing for the creation of new and exciting optical detection methods. This project aims to look at one particular way to perform optical detection, with the topic of plasmonics being the chosen area. The use of plasmonics allows for the development of optical detectors that can be used beyond the diffraction limit (into the nanoscale region) and also have broadband nature which means the detector can have its spectral response tuned. Through simulations, the tunability of plasmonic optical detectors was investigated and analyzed by measuring the reflectance response of the structure with respect to the wavelength of the incident light. Specific simulation software allowed for the construction of pre-designed plasmonic structures that could then be tested to see how alterations within certain structural parameters affected the spectral response of the structure. 2D simulations were done that investigated the dielectric material used, the metal used and the incident wavemode. The results from these simulations were not very accurate and would need to be performed again to gauge a better understanding of how these parameters affect the response. 3D simulations were also performed that investigated the metal used, the dielectric material used, the dielectric thickness, NP diameter, NP height, NP shape and NP pitch. The results from these simulations were very successful with clear wavelength shifts when these parameters were altered hence proving their tunable nature. The successful results also agreed with the theory of plasmonics and previous publications. Some of the 3D simulations however were not successful and would need to be implemented again. The final part of the project looked at applying the knowledge gained from the simulations to make a color palette, which is a potential application for the plasmonic structures used. The color palette was successfully constructed and had similar results to previous publications. Remove